2014
DOI: 10.1152/ajplung.00040.2014
|View full text |Cite
|
Sign up to set email alerts
|

ENaC activity and expression is decreased in the lungs of protein kinase C-α knockout mice

Abstract: We used a PKC-α knockout model to investigate the regulation of alveolar epithelial Na(+) channels (ENaC) by PKC. Primary alveolar type II (ATII) cells were subjected to cell-attached patch clamp. In the absence of PKC-α, the open probability (Po) of ENaC was decreased by half compared with wild-type mice. The channel density (N) was also reduced in the knockout mice. Using in vivo biotinylation, membrane localization of all three ENaC subunits (α, β, and γ) was decreased in the PKC-α knockout lung, compared w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 54 publications
1
24
0
Order By: Relevance
“…It seems that there are different roles for ROS in the regulation of ENaC, both inhibitory and stimulatory. Elevated ROS could cause a decrease in ENaC activity, as seen in the PKC-α knockout lung [ 1 , 51 ], as well as previous literature had reported that ROS had a stimulatory effect on ENaC activity [ 49 , 52 ]. The discrete effects of extracellular and intracellular ROS on different cell and tissue models might regulate alveolar ENaC differently.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It seems that there are different roles for ROS in the regulation of ENaC, both inhibitory and stimulatory. Elevated ROS could cause a decrease in ENaC activity, as seen in the PKC-α knockout lung [ 1 , 51 ], as well as previous literature had reported that ROS had a stimulatory effect on ENaC activity [ 49 , 52 ]. The discrete effects of extracellular and intracellular ROS on different cell and tissue models might regulate alveolar ENaC differently.…”
Section: Discussionmentioning
confidence: 99%
“…AFC appears to play an essential part in lung fluid balance in both physiological and pathological conditions, as studies have showed that patients suffering from acute lung injury or the more severe acute respiratory distress syndrome have dysfunctional alveolar fluid clearance [ 37 ]. Much evidence has confirmed that Na + reabsorption is a vital means of maintaining lung fluid balance and that ENaC plays a key role in Na + reabsorption [ 1 , 3 , 38 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The receptor for advanced glycation end-products (RAGE) regulated lung fluid balance via PKC-gp91 phox signaling to ENaC (Downs, Kreiner, Johnson, Brown, & Helms, 2014). Kinases SGK, PKC and PKA up-regulate ENaC activity in a variety of epithelial cell systems (Baines, 2013; Eaton, Yue, Eaton, & Bao, 2014). Some of these signaling molecules and pathways are well known components of signal transduction by ET-1.…”
Section: Lung Smooth Muscle and Distal Colon: Et-1 And Enacmentioning
confidence: 99%